Perancangan Database dalam Sistem Pembelajaran Matematika Dasar Berbasis Konsep Guru dengan Peta Pikir - Harini, Luh Putu Ida; Astawa, I Gede Santi (Jurnal Ilmu Komputer; Vol 13 No 2 (2020): Jurnal Ilmu KomputerDO - 10.24843/JIK.2020.v13.i02.p07, 2020)
The basic concept of mathematics is a mathematical material that is very important to be mastered by students. One of the efforts to increase student understanding is the creation of a computer-based learning system that is able to provide material according to student understanding. Research on the use of mind maps in developing the concept of learning mathematics by teachers in increasing student understanding makes the background for research on the use of mind maps as a reference for making this computer-based learning system. From the results of the preliminary research that has been done, it can be concluded that the use of the concept of mind maps as a method of helping student learning has gone well according to user needs. And from the results of small scale testing by 10 teachers, the results obtained 75% of respondents rated the prototype "Very Good" and 25% rated "Good" Keywords : mind map, learning, computer-based systems